DU Is Induced by Low Levels of Urinary ATP in a Rat Model of Partial Bladder Outlet Obstruction: The Incidence of Both Events Decreases after Deobstruction - Luís Vale; Ana Charrua; Helena Cavaleiro; Rita Ribeiro-Oliveira; António Avelino; Tiago Antunes-Lopes; António Albino-Teixeira; Francisco Cruz (Advances in Urology)
Objectives. To investigate, in initial phases of bladder outlet obstruction (BOO), the urinary ATP levels, the incidence of detrusor underactivity (DU), and if they change after deobstruction. Methods. Adult female Wistar rats submitted to partial BOO (pBOO) and sham-obstruction were used. Cystometry was performed 3 or 15 days after pBOO and fluid was collected from the urethra for ATP determination. Bladders were harvested for morphological evaluation of the urothelium. DU was defined as the average of voiding contractions (VC) of sham-operated animals, with 3 SD at 15 days after the sham surgery. In another group of animals in which pBOO was relieved at 15 days and bladders were let to recover for 15 days, the incidence of DU and ATP levels were also accessed. The Kruskal–Wallis test was followed by Dunn’s multiple comparisons test, and Spearman’s correlation test was used. Results. DU was present in 13% and 67% of the bladders at 3 and 15 days after pBOO, respectively, and in 20% of the bladders at 15 days after deobstruction. ATP levels were significantly lower in DU/pBOO versus sham and non-DU/pBOO rats. A strong positive correlation between ATP levels and VC/min was obtained (r = 0.63). DU bladders had extensive areas in which umbrella cells appeared stretched, the width exceeding that presented by sham animals. Conclusions. Low urothelial ATP parallels with a high incidence of DU early after pBOO.